Menumbuhkan Nasionalisme melalui Inovasi Game Pada Peringatan Hari Kemerdekaan di Sekolah SMA Nurul Jadid - Ibnu Syarofi; Mohammad Sofyan Adi Pranata (Elsalima (Salam Institute), 2026)
Nationalism among Generation Z students faces challenges from globalization and foreign cultural influences that overshadow national identity. This community service aimed to foster nationalism through innovative educational games during Independence Day celebrations at SMA Nurul Jadid. The activity involved 180 female students from grades X, XI, and XII through a participatory and collaborative approach in four stages: preparation, development, implementation, and evaluation. Three types of educational games were developed: Interactive Quiz on Independence History, Role Playing Game